Proteic values in elderly institutionalized in the municipality of Santa Clara - Naivy Sánchez Vera; Maikel Aguila López; Lutgarda María Pérez de Alejo Rodríguez; Carmen Xiomara More Chang; Yusimí González Álvarez (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: The Cuban population faces today the phenomenon of aging.  Objective: To characterize  proteic values in institutionalized elderly.  Methods: A  descriptive and cross-sectional study of elderly  with 60 years and more who lived in the home for the aged ofSanta Clara,  Villa Clara, was carried out from January, 2016 to December, 2017. The universe was constituted by 366, of which a non probabilistic sample of 182 was selected.  Seric values of total proteins were determined, albumin, globulins and immunoglobulins (A, G, M), as well as   C3 and C4 supplement.  Results: There was a  prevalence of female sex (53.3%),  white skin color (78.6%),  60-74  ages, overweight as nutritional state  and history of osteoarthrosis,  hypertension and hyperlipemia. Total proteins presented values of 74.00 ± 5.461 and  immunoglobulins: IgA 2.57 ± 0.944; IgG 11.06 ± 2.094 and IgM 1.13 ± 0.612.    Conclusions:  a progressive decrease of total proteins , albumin, globulins and immunoglobulins (G, A and M) took place,  they stayed in the range of normality but their  means values were near  the inferior limit of such range. With the advance of  age this phenomenon increased and a higher decrease took place. The  C3 and C4 complement didn't present variations related to the normal value.